2011
DOI: 10.1007/s10499-011-9470-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein requirement for fingerling Channa punctatus (Bloch), based on growth, feed conversion, protein retention and biochemical composition

Abstract: An 8-week feeding trial was conducted in a flow-through system (1-1.5 L min -1 ) at 27°C to determine dietary protein requirement for Channa punctatus fingerlings (4.58 ± 0.29 g) by feeding six isocaloric diets (18.39 kJ g -1 , gross energy). Diets containing graded levels of protein (300, 350, 400, 450, 500 and 550 g kg -1 ) were fed to triplicate groups of fish to apparent satiation at 09:00 and 16:00 h. Maximum absolute weight gain (AWG; 8.11 g fish -1 ), specific growth rate (SGR; 1.82%) and best feed conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 29 publications
8
45
0
2
Order By: Relevance
“…Zehra and Khan reported that growth performance of Corydoras punctatus fingerlings in response to varying levels of dietary protein levels, at 450 g/kg FCR was 1.48 [43]. In this present study, the highest FCR was observed in SW4 diet (3.17) and SW2 diet (2.49) and the lowest FCR was observed in GA2 diet and GA5.…”
Section: Discussionsupporting
confidence: 51%
“…Zehra and Khan reported that growth performance of Corydoras punctatus fingerlings in response to varying levels of dietary protein levels, at 450 g/kg FCR was 1.48 [43]. In this present study, the highest FCR was observed in SW4 diet (3.17) and SW2 diet (2.49) and the lowest FCR was observed in GA2 diet and GA5.…”
Section: Discussionsupporting
confidence: 51%
“…It is well known that protein is an expensive and the most important nutrient for feed formulation (Wee and Tacon, 1982;Zehra and Khan, 2011). In the present study, growth (weight gain and SGR) and survival of pengba increased significantly (p<0.05) with increase in dietary protein levels from 25 to 45%, and thereafter decreased at 50% protein level.…”
Section: R Ramesh Et Alsupporting
confidence: 52%
“…The experimental diets were analyzed for niacin and found to contain 0, 8.21, 18.64, 27.43, 36.82, 47.91 and 56.28 mg/kg dry diet. The dietary protein requirement was fixed as per reported by Zehra and Khan, () for C. punctatus . Mineral premix was prepared as per Halver ().…”
Section: Methodsmentioning
confidence: 99%
“…Vitamins are involved in all the biological functions that allow the animals to use energy and protein for maintenance, growth, health, feed conversion and reproduction. If one or more vitamins are deficient, increase in the other nutrients will not overcome the deficiency and permit these functions to occur (Kamalzadeh, Ila, & Heydarnejad, ; Zehra & Khan, , ). The traditionally defined water‐soluble vitamins seem to be essential to all examined farmed fish species so far (Waagbo, ).…”
Section: Introductionmentioning
confidence: 99%